Tinjauan Kualitas Jaringan Jalan untuk Peningkatan Produksi pada Pabrik Pengolahan Kelapa Sawit - Arnol, Irwan; Bakhri, Syamsul; Darsono, Darsono (Green Publisher Indonesia, 2025)
The road network system in the Palm Oil Plantation area is centered on the Main road network that serves the transportation of palm oil production directly from the Plantation to the Processing Factory with varying distances. The road network system provides easy accessibility for transportation facilities to carry all plantation products to be produced into Crude Palm Oil (CPO). The study was conducted at PT. Perkebunan Nusantara XIV (Persero) Malili Plantation Unit and PT. Bumi Maju Sawit located in Angkona District, East Luwu Regency and continued to the Malili Plantation Unit/Plantation location, East Luwu. This study aims to determine the level of accessibility of palm oil transport vehicles, the quality of the road network in existing conditions and to determine the effect of road quality on increasing CPO production results. The research method uses a survey method with a descriptive approach. percentage value of accessibility level parameters 1) Travel intensity, on average respondents travel 1-2 times a day with a percentage of 52.50%; 2) Travel time, 52.92% of respondents need more than 90 minutes to reach the palm oil processing factory; 3) Ease of travel, 66.25% of respondents stated that it was difficult to travel through the existing road access to the factory; 4) Travel comfort, 41.25% of respondents stated that it was still not comfortable through the existing road access; and 5) 71.25% of respondents stated that traffic flow accessibility was still not smooth.